The Effectiveness of 6-3-5 Brainwriting Strategy in Teaching Writing Skill - Sulaiman, Sulaiman; Yuliani, Sri; Qathrunnada, Sausan (International Journal of Education Research and Development, 2024)
The primary aim of this research is to evaluate the effectiveness of the 6-3-5 brainwriting methodology in instructing writing proficiency to students in the eighth grade at SMP Negeri 21 Palembang. A genuine experimental study approach was employed by the researchers, utilising a sample size of 64 students. The researchers employed pretests and posttests as tools for data collection. The present study employed paired and independent sample t-tests, as well as additional t-tests, for the purpose of data analysis. The findings from the paired t-test analysis indicated that the experimental group obtained an average score of 70.94 on the pretest, while the control group obtained a baseline score of 39.69. On the posttest, the experimental group achieved an average score of 84.53, whereas the control group exhibited an average score of 45.94. The identified discrepancies suggest that there is a substantial disparity in the mean scores of the two groups; the experimental group exhibits superior scores when compared to the control group's pretest-posttest results. In addition, the t-value produced by the independent sample t-test was 0.000, which is less than the predetermined level of significance of 0.05. This finding indicates that the 6-3-5 brainwriting technique effectively guided learners through the process of constructing recount narratives.